Efficient Access to Chromeno[4,3-b]quinolines Related to Dependensin - Dobrowolski, Jeremy C.; Fraser, Benjamin H.; Bhadbhade, Mohan; Black, David StC.; Kumar, Naresh (Synlett, 2017)
We report a robust synthesis of novel chromeno[4,3-b]quinoline derivatives structurally similar to the natural product dependensin. The target compounds are accessed through the acid-catalysed condensation of 2-aminoacetophenones or 2-aminochalcones with substituted flavanones, which are in turn obtained from 2-hydroxyacetophenones and benzaldehydes.
Keywords: dependensin; chromeno[4,3-b]quinoline; flavanone; acid-catalysed synthesis